1985
DOI: 10.1002/ar.1092110413
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of neurotensin in hamster adrenal medulla

Abstract: Neurotensin-like immunoreactivity was localized in nerve fibers and terminals of hamster adrenal medulla at light and electron microscopy using the peroxidase-antiperoxidase method. Numerous varicose neurotensin-immunoreactive nerves and terminals were found among nonlabeled cell groups situated peripherally in the adrenal medulla. Combined formaldehyde-glutaraldehyde (Faglu) fluorescence and immunohistochemistry of the same vibratome section showed that only norepinephrine cells were innervated by neurotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Islands of noradrenaline cells are surrounded by a dense network of cholinesterase-positive structures (Allen et al 1958;Eränkö 1959;Lewis and Shute 1968). Immunohistochemical studies demonstrated that neurotensincontaining nerves innervate only noradrenaline cells in the hamster adrenal medulla (Pelto-Huikko et al 1985b), but that enkephalin- (Pelto-Huikko et al 1985a) and GABA- (Oomori et al 1993) immunoreactive nerve fibers are numerous around adrenaline cells. These findings showed that adrenaline cells and noradrenaline cells differ in degree of innervation and type of nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Islands of noradrenaline cells are surrounded by a dense network of cholinesterase-positive structures (Allen et al 1958;Eränkö 1959;Lewis and Shute 1968). Immunohistochemical studies demonstrated that neurotensincontaining nerves innervate only noradrenaline cells in the hamster adrenal medulla (Pelto-Huikko et al 1985b), but that enkephalin- (Pelto-Huikko et al 1985a) and GABA- (Oomori et al 1993) immunoreactive nerve fibers are numerous around adrenaline cells. These findings showed that adrenaline cells and noradrenaline cells differ in degree of innervation and type of nerves.…”
Section: Discussionmentioning
confidence: 99%
“…ChAT‐only immunoreactive nerve fibers were in contact with NA cells and the number of varicosities of ChAT‐immunoreactive nerve fibers in NA cell areas was almost more than twice that of the nerve fibers in A cell areas. Previous immunohistochemical studies have demonstrated that neurotensin and substance P immunoreactive nerve fibers only innervated NA cells in the hamster and rat adrenal medulla (Pelto‐Huikko et al, ; Murabayashi et al, ), whereas enkephalin and GABA‐immunoreactive nerve fibers were only numerous in A cells (Pelto‐Huikko et al, ; Oomori et al, ; Iwasa et al, ). Furthermore, AChE positive nerve fibers, ChAT, vesicular acetylcholine transporter and neurocalcin immunoreactive nerve fibers were in dense contact with NA cell groups compared to A cell groups (Allen et al, ; Eränkö ; Lewis and Shute, ; Iino et al, ; Iwasa et al, ; Murabayashi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Donckier et al(1988) and Vesely et al(1988) found that circulating ANP increased during surgery for pheochromocytoma and returned to normal after removal of the tumor and they suggested that the pheochromocytoma may contain ANP within the tumor cells. Pheochromocytoma had been reported to secrete neurotransmitter biogenic amines (dopamine, noradrenalin, adrenalin, serotonin, histamine, and melatonin) and various peptides including calcitonin (Hassoun et al, 1984), enkephalins (Lundberg et al, 1979), somatostatin (Lundberg et al, 1979), vasoactive intestinal polypeptide (Hassoun et al, 1984), dynorphin (Yoshimasa et al, 1981), renin (Naruse et al, 1983), MSH (Giraus et al, 1981), beta-endorphin (Hassoun et al, 1984), neuropeptide Y (Lundberg et al, 1986), neurotensin (Pelto-Huikko et al, 1985), ACTH (Hassoun et al, 1984), CRH (Suda et al, 1984), GHRH (Sano et al, 1986), parathormone, chromogranin A, motilin, vasopressin, cholecystokinin, insulin, neuron-specific enolase and substance P (Sheps et al, 1988). Our finding ANP in pheochromocytoma provides additional evidence for the neural crest origin of multisecretory APUD cells.…”
Section: Immunoelectron Microscopymentioning
confidence: 99%
“…Pheochromocytoma, an adrenal medullary neoplasm, has been known to secrete biogenic amines and various peptide hormones including somatostatin (Lundberg et al, 1979), vasoactive intestinal polypeptide (Hassoun et al, 1984), enkephalins (Lundberg et al, 1979) neurotensin (Pelto-Huikko et al, 1985), dynorphin (Yoshimasa et al, 1981), ACTH Hassoun et al, 1984), CRH (Suda et al, 1984) and GHRH (Sano et al, 1986), etc. (for review, see Sheps et al, 1988 Light microscopic immunohistochemistry Using the immunohistochemical technique, the control human right atrial cardiocytes were positively stained with ANP antiserum at a dilution 1:600.…”
mentioning
confidence: 99%